Circumcision with the Plastibell Device in Hooded Prepuce or Glanular Hypospadias - Seyed A. Mousavi; Hamid Mohammadjafari (Advances in Urology)
Purpose. To retrospectively review our experience in infants with glanular hypospadias or hooded prepuce without meatal anomaly, who underwent circumcision with the plastibell device. Although circumcision with the plastibell device is well described, there are no reported experiences pertaining to hooded prepuce or glanular hypospadias that have been operated on by this technique. Materials and Methods. Between September 2002 and September 2008, 21 children with hooded prepuce (age 1 to 11 months, mean 4.6 months) were referred for hypospadias repair. Four of them did not have meatal anomaly. Their parents accepted this small anomaly and requested circumcision without glanuloplasty. In all cases, the circumcision was corrected by a plastibell device. Results. No complications occurred in the circumcised patients, except delayed falling of bell in one case that was removed by a surgeon, after the tenth day. Conclusion. Circumcision with the plastibell device is a suitable method for excision of hooded prepuce. It can also be used successfully in infants, who have miniglanular hypospadias, and whose parents accepted this small anomaly.